The prevalence of hepatitis C virus infection in patients with diabetes mellitus - Bahcecioglu, I.H.; Ozkan, Y.; Celebi, S.; Donder, E. (My University, 1999)
Purpose: In this study, we aimed to determine the prevalence of hepatitis C virus (HCV) infection in patients with diabetes mellitus. We evaluated the relationship between HCV infection and diabetes mellitus in terms of the duration of diabetes, type of diabetes, treatment, hospitalization, operation and history of blood transfusion. Patients and methods: A total of 100 patients with diabetes mellitus and a total of 100 normal healthy individuals were enrolled in the study. Eighty-eight of the patients were type 2 diabetes and 12 of the patients were type 1 diabetes. In patients and controls anti-HCV antibodies, HbsAg and anti-HBs antibodies were detected with the third generation ELISA test. Results: The prevalence of anti-HCV in patients with diabetes mellitus was higher than the controls (7%, 1%, respectively). The difference was statistically significant (p<0.05). All of the anti-HCV positive cases were type 2 diabetes mellitus. Hospitalization was found more frequently in patients with type 1 diabetes mellitus. There was no history of blood transfusion in cases with anti-HCV positivity. Alanine aminotransferase level was higher than the normal level in 85.7% of anti-HCV positive cases and 17.2% of control cases. The difference was statistically significant (p<0.05). Conclusion: HCV infection appears to be related with type 2 diabetes mellitus. This relationship between HCV infection and diabetes mellitus indicates that HCV itself may be diabetogenic. Further investigation should be performed to establish the diabetogenic role of HCV.
Diabetes mellituslu hastalarda hepatit C virus infeksiyon sikligi
Keywords: Diabetes mellitus; Hepatitis C